Spotlight on VET : compilation; vocational education and training systems in Europe 2024 - (:unkn) unknown (Publications Office, 2024)
„Building on individual country Spotlights, this publication provides an overview of VET systems with their distinctive qualities, such as main accession and progression routes for learners; types and levels of qualifications they lead to; types of programmes, delivery modes, work-based learning ratio and duration. In addition to the system charts, it also briefly reflects on current challenges and recent VET policy initiatives.“ (editor; BIBB-Doku)
Keywords: S System beruflicher Bildung; I 2.2 Europa; 370; Berufsbildung; Berufsbildungssystem; Österreich; Bulgarien; Zypern; Tschechien; Dänemark; Estland; Finnland; Frankreich; Bundesrepublik Deutschland; Griechenland; Lettland; Litauen; Luxemburg; Niederlande; Norwegen; Polen; Portugal; Rumänien; Slowakei; Schweden